Simultaneous Improvement in Dissolution Behavior and Oral Bioavailability of Naproxen via Salt Formation - Xian-Rui Zhang; Bao-Lin Wu; Jing-Jing Han; Jin-Qing Li (Crystals, 2024)
Naproxen (NAP) is a non-steroidal anti-inflammatory drug (NSAID) that belongs to the arylpropionic acid class. Classified as a Biopharmaceutical Classification System (BCS) class II drug, NAP exhibits low water solubility, thus resulting in restricted oral bioavailability. This study aimed to evaluate the effectiveness of pharmaceutical salts in enhancing the solubility and oral bioavailability of NAP. Two novel NAP salts, specifically naproxen-ethylenediamine (NAP-EDA) and naproxen-trometamol (NAP-TRIS), were synthesized using a 2:1 and 1:1 stoichiometric ratio, respectively. The NAP-EDA and NAP-TRIS powders were thoroughly characterized using single-crystal X-ray diffraction (SXRD), powder X-ray diffraction (PXRD) and differential scanning calorimetry (DSC), providing a comprehensive understanding of their structural and thermal properties. Additionally, the solubilities and dissolution rates of NAP-EDA and NAP-TRIS salts were assessed in water and a pH 6.86 phosphate buffer. Notably, the solubility of NAP-TRIS salt increased markedly, by 397.5-fold in water and 6.2-fold at pH 6.86. Furthermore, in vivo pharmacokinetic studies in rats revealed that NAP-TRIS salt displayed faster absorption and higher peak blood concentrations compared to NAP. These results indicate that the NAP-TRIS salt effectively enhanced the solubility and oral bioavailability of naproxen. In conclusion, this study underscores the potential of pharmaceutical salts, particularly NAP-TRIS, in improving the solubility and oral bioavailability of drugs with low aqueous solubility, presenting a promising avenue for advancing drug delivery and therapeutic outcomes.